Efectiveness of Whey Protein Consentrates and Dextrins to Maintain Viability of Lactic Acid Bacteria in Frozen Dried Starter Yoghurt - Karinawatie, Shanty; Kusnadi, Joni; Martati, Erryana (Jurnal Teknologi Pertanian, 2008)
The aim of this research was to investigate the effect of dextrins (0, 35, 40 and 45% (w/w) as cryoprotectant agent and whey protein concentrates (WPC) (0, 2 and 4% (w/v)) as nutrition which promote lactic acid bacteria (LAB) growth, to maintain viability of LAB in frozen dried yoghurt starter. The result of this study showed that WPC and dextrin can maintain LAB yoghurt in frozen dried starter, effectively. WPC concentrations showed very significant difference on LAB total and water content. Dextrin concentrations showed very significant difference on all parameters. The best treatment resulted from the combination of 4% WPC and 45% dextrin added. The characteristics were LAB total of 8,21 log CFU/g, water content of 5,28% and lightness 71. Yoghurt product made by the best treatment of frozen dried starter were not give significant differences with yoghurt product using liquid starter on LAB total, pH, acidity total and reducing sugar. To make yoghurt, the percentage of frozen dried starter was 7,45% (w/v) whereas the percentage of liquid starter was 2% (w/v).Key Word : LAB viability, frozen dried starter, freeze drying, dextrin, WPC